2006
DOI: 10.4049/jimmunol.177.6.4037
|View full text |Cite
|
Sign up to set email alerts
|

Neutrophil Signaling Pathways Activated by Bacterial DNA Stimulation

Abstract: We have previously shown that bacterial DNA activates human neutrophils in a CpG-independent manner. In this study, we have characterized the signaling pathways involved in the activation mechanism. We found that p38 MAPK, ERK1/2, and JNK pathways, as well as the PI3K/Akt pathway, are activated by bacterial DNA. We also determined that bacterial DNA induces NF-κB and AP-1 activation. When analyzing the role of these pathways on neutrophil functions, we observed that up-regulation of CD11b triggered by bacteria… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
40
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(45 citation statements)
references
References 52 publications
(63 reference statements)
4
40
0
Order By: Relevance
“…Neutrophils, in fact, can readily respond to CpG oligodeoxynucleotides in terms of CXCL8 production and inhibition of apoptosis because they express their cognate receptor, TLR9 (4). Other findings demonstrated that extracellular bacterial DNA can trigger, through an unidentified receptor, another pathway functioning in a TLR9-and CpG-independent, but MyD88-dependent, manner (59). Our new observations additionally suggest that human neutrophils possess intracellular sensor system(s) that allow(s) the recognition of foreign and potentially dangerous DNA and, consequently, the induction of a distinct and potent immune response (60).…”
Section: Discussionmentioning
confidence: 99%
“…Neutrophils, in fact, can readily respond to CpG oligodeoxynucleotides in terms of CXCL8 production and inhibition of apoptosis because they express their cognate receptor, TLR9 (4). Other findings demonstrated that extracellular bacterial DNA can trigger, through an unidentified receptor, another pathway functioning in a TLR9-and CpG-independent, but MyD88-dependent, manner (59). Our new observations additionally suggest that human neutrophils possess intracellular sensor system(s) that allow(s) the recognition of foreign and potentially dangerous DNA and, consequently, the induction of a distinct and potent immune response (60).…”
Section: Discussionmentioning
confidence: 99%
“…Several reports indicate the presence of JNK1 in human neutrophils, although it has also been reported that JNK2 is the dominant isoform in these cells (45)(46)(47)(48)(49). More interestingly, it has been reported that inflammatory cytokine production in human PMN is independent of JNK and the downstream transcription factor complex AP-1 (50).…”
Section: Discussionmentioning
confidence: 99%
“…In particular, Akt activation induces modulation of Bcl-2 family proteins such as Mcl-1 and phospho-Bad (39,40) and could therefore be involved in the inhibitory effect of CpG-DNA on our patient's PMN apoptosis. In addition, it has been reported that class I PI3K-catalytic subunits can lead to phosphorylation of ERK1/2 and p38MAPK (9,10,41,42); activation of these signaling pathways has been implicated in the up-regulation of CD11b expression (43,44) and L-selectin shedding (45,46) after PMN treatment with various inflammatory stimuli. In keeping with these data, we demonstrated that CpG-DNA-induced modulation of CD11b and Lselectin on the surface of our patient's PMNs is partially inhibited by pharmacological inhibitors of ERK1/2 and p38MAPK; furthermore, we found a CpG-DNA-induced increase in phosphorylation of ERK1/2 and p38MAPK in the patient's PMNs, which was reduced by PI3K inhibitors.…”
Section: Discussionmentioning
confidence: 99%